Resolution of symptoms after Heller's cardiomyotomy with DOR fundoplication versus endoscopic balloon dilatation in patients with achalasia Cardia at tertiary care hospital - Shahriyar Ghazanfar; Sajida Qureshi; Ali Rasheed; Fahad Memon; Mohammad Saeed Quraishy (Journal of the Pakistan Medical Association, 2021)
Objective: The objective was to compare symptoms improvement following Heller's myotomy with DOR fundoplication (HM-DOR) and endoscopic pneumatic dilatation (PD) for the treatment of achalasia cardia at one year follow up. Methods: This prospective comparative study was conducted at department of upper GI and minimally invasive surgery, Civil hospital Karachi from February 2016- January 2019. All patients diagnosed as a case of achalasia cardia on esophageal manometry were included in this study. Subjects were grouped into two treatment groups: Endoscopic Pneumatic Dilatation(PD) and laparoscopic Heller's myotomy with DOR fundoplication (HM-DOR). Results: A total of 42 patients were taken into study, of which 21 patients were randomly assigned in each of the two groups (surgery and endoscopic). Mean age of patients undergoing laparoscopic Heller’s myotomy and endoscopic pneumatic balloon dilatation was 34±8.59 and 37±12.87 years respectively. Treatment success in PD group was 52% (11/21) as compared to HM-DOR group which was 76% (16/21). Post Eckardt scores reduction at 1 year follow up between PD and HM-DOR were statistically significant (p<0.001). Patient satisfaction measured by likert's scale was significantly more in the surgery group. Conclusion: The efficacy of HM appears to be greater than PD for improvement in dysphagia and overall patients satisfaction score over a 1 year follow up period. Keywords: Esophageal achalasia, Heller’s myotomy (HM), Endoscopic pneumatic dilatation (PD). Continuous...